(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2017)
My desire to read ‘Inventing the future’ emerged after happening upon a short provocation called the ‘Accelerationist Manifesto’, also written by this book’s authors (political theorist Nick Srnicek and sociologist Alex Williams) in 2013. These are both polemical works which, whilst not directly about education, surface a number of debates pertinent to educators working for social justice. Accelerationism—a peculiar mix of sci-fi and political theory—starts from the premise that a moribund left must learn to let go of its anachronistic tendencies (the authors label these tendencies ‘folk politics’), by counter-intuitively embracing the breakneck speed of life and labour under neoliberal techno-capitalism. This, as I understand it, is a speculative response to capitalism’s ‘moving contradiction’ of labour, ‘both source of value, and squeezed out by the machine’ (Noys, 2014, p. 97), which it attempts to burst through by embracing full-automation as one necessary condition of a post-capitalist, post-work utopia.